Assessing the seam strength of ultrasonically welded polyester and polypropylene spunbond nonwovens. (30th June 2022) - ÇİNÇİK, Emel; İNAN ÜSTÜN, Aynur
The durability of the products such as personal protective clothes and facemasks are crucial for human health as these products prevent the spread of disease. This study aims to investigate the seam strength of ultrasonically welded spunbond nonwovens used for personal protective clothes, facemasks, diapers and determine the best welding parameters for optimum seams. For these purposes, polyester and polypropylene spunbond nonwoven fabrics with different areal weights were ultrasonically welded by changing process parameters such as vibration frequency (%-kHz) and welding pressure (bar). The welded samples were evaluated according to the standard test method for seam strength and experimental data obtained from tests were statistically assessed by generating models and regression equations. The best seam strength for polyester nonwovens with different areal weights was achieved with 80% vibration amplitude and 1 bar or 1.5 bar welding pressures. In contrast, ultrasonic welding applied with 0.5 bar welding pressure and 63% or 70% vibration amplitudes resulted in the highest seam strengths for polypropylene nonwovens.